A Novel Chitin‐Based Purification System Using GAL1 Fusion Tags: Enhancing Recombinant Protein Production While Retaining Biological Activity - Yao‐Kuang Tseng; Yun‐Heng Lu; Yun Liu; Zhi‐Wei Weng; Yu‐Tzu Lin; Chih‐Hsuan Tsai; Yueh‐Lung Wu; Rong‐Nan Huang (Microbial Biotechnology)
ABSTRACT Efficient and economical purification methods are crucial for the commercial production of recombinant proteins with biomedical applications. In this study, we developed an affinity chromatography system that leverages the polysaccharide‐binding properties of galectin‐1 (GAL1) as a protein tag. The known GAL1‐binding material, chitin, was used as the purification matrix. Melittin (MELT), a bee venom peptide known for its antimicrobial and anti‐inflammatory properties with commercial potential, was chosen to validate this system. The GAL1–MELT fusion protein was expressed in Escherichia coli (E. coli) and successfully purified using a chitin‐based matrix with sodium dodecyl sulfate (SDS) as a removable eluant. This method demonstrated higher purification efficiency compared to the His‐tag/Ni‐NTA approach, indicating that the GAL1/chitin system could serve as a superior alternative. The GAL1–MELT fusion protein retained strong antibacterial and anti‐inflammatory activities, as well as collagen content modulation effects, confirming that MELT maintained its bioactivity. Apart from that, the GAL1–DsRed fusion protein was used as an additional protein target to evaluate the efficiency of the chitin‐based column. Notably, all experiments were conducted without tag cleavage, showing that enzyme treatments for MELT isolation were unnecessary. This study highlights the potential of GAL1–polysaccharide interactions as a cost‐effective and highly efficient alternative method for recombinant protein purification.